Late onset post-keratoplasty astigmatism in patients with keratoconus. Issue 3 (20th February 2004) - Lim, L; Pesudovs, K; Goggin, M; Coster, D J
Abstract : Aim: 10 eyes of 10 patients are reported where progression of keratoconus in the host cornea occurred more than 10 years after penetrating keratoplasty with resultant increase in astigmatism. The technique and results of graft refractive surgery in seven eyes are presented. Methods: The clinical features and management of these patients were retrospectively analysed. Graft refractive surgery involved an incision at the graft-host junction adjacent to the host thinning with compressive resuturing. Astigmatic changes were calculated using vector analysis. Results: There were seven men and three women with a mean age of 41.2 years. The average age when undergoing penetrating keratoplasty in the affected eye was 28.4 years and the average time after penetrating keratoplasty until keratoconus appeared in the host cornea defined by host thinning was 13.5 years. The mean cylinder power before host thinning was noted was 5.07D (SD 2.19) and the mean after host thinning was 11.0D (2.53). The mean vector calculated disease induced astigmatism magnitude was 7.59D (3.09). Graft refractive surgery was performed in seven eyes. The mean cylinder power before and after graft refractive surgery was 11.28D (2.15) and 7.09D (5.53) respectively. The surgically induced astigmatism vector magnitude was 7.36D (4.88). Conclusion: Progression of keratoconus in the host cornea late after penetrating keratoplasty is characterised by a large astigmatic change where the flat axis of astigmatism passes through an area of host thinning visible on slit lamp examination. Compressive resuturing performed in the area of host thinning resulted in satisfactory reduction of astigmatism.